Omeprazole Increases Survival Through the Inhibition of Inflammatory Mediaters in Two Rat Sepsis Models. Issue 3 (27th March 2022) - Kotsuka, Masaya; Hashimoto, Yuki; Nakatake, Richi; Okuyama, Tetsuya; Hatta, Masahiko; Yoshida, Terufumi; Okumura, Tadayoshi; Nishizawa, Mikio; Kaibori, Masaki; Sekimoto, Mitsugu
ABSTRACT: Background: Omeprazole (OMZ) is a proton pump inhibitor that is used to reduce gastric acid secretion, but little is known about its possible liver protective effects. This study investigated whether OMZ has beneficial effects in rat septic models of LPS-induced liver injury after D-galactosamine (GalN) treatment and 70% hepatectomy (PH), and to determine the mechanisms of OMZ in an in vitro model of liver injury. Methods: In the in vivo models, the effects of OMZ were examined 1 h before treatments in both models on survival, nuclear factor (NF)-κB activation, histopathological analysis, and proinflammatory mediator expression in the liver and serum. In the in vitro model, primary cultured rat hepatocytes were treated with IL-1β in the presence or absence of OMZ. The influence of OMZ on nitric oxide (NO) product and inducible NO synthase (iNOS) induction and on the associated signaling pathway was analyzed. Results: OMZ increased survival and decreased tumor necrosis factor-alpha, iNOS, cytokine-induced neutrophil chemoattractant 1, IL-6, and IL-1β mRNA expression, and increased IL-10 mRNA expression in the livers of both GaIN/LPS- and PH/LPS-treated rats. Necrosis and apoptosis were inhibited by OMZ in GaIN/LPS rats, but OMZ had no effects on necrosis in PH/LPS rats. OMZ inhibited iNOS induction partially through suppression of NF-κB signaling in hepatocytes. Conclusions: OMZ inhibited the induction of several inflammatory mediators, resulting in the prevention of LPS-induced liver injury after GalN liver failure and PH, although OMZ showed different doses and mechanisms in the two models.